2010
DOI: 10.1016/j.devcel.2010.07.007
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin Primes Organizer Gene Expression by Recruiting a Histone H3 Arginine 8 Methyltransferase, Prmt2

Abstract: Summary An emerging concept in development is that transcriptional poising pre-sets patterns of gene expression in a manner that reflects a cell’s developmental potential. However, it is not known how certain loci are specified in the embryo to establish poised chromatin architecture as the developmental program unfolds. We find that, in the context of transcriptional quiescence prior to the midblastula transition in Xenopus, dorsal specification by the Wnt/β-catenin pathway is temporally uncoupled from the on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(103 citation statements)
references
References 72 publications
2
99
1
1
Order By: Relevance
“…zebrafish and Xenopus embryos. 5,28,29 This assay allows us to evaluate global transcriptional activity in combination with N:C ratio on an individual cell basis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…zebrafish and Xenopus embryos. 5,28,29 This assay allows us to evaluate global transcriptional activity in combination with N:C ratio on an individual cell basis.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, analyses of RNA synthesis and large-scale gene expression have found zygotic gene expression in Drosophila, Xenopus and zebrafish well before the MBT. 1,[4][5][6]45,46 Additionally, gene expression profiling data from haploid and diploid Drosophila embryos suggest more complex regulation of zygotic transcription, with distinct subsets of zygotic transcripts that depend either on time or on the N:C ratio. 1 Our studies also provide insight into cell cycle remodeling at the MBT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence suggests that alterations in DNA methylation and histone modifications around the time of MBT are important for zygotic gene activation [47,[87][88][89][90]. Similarly, β-catenin recruits the arginine methyltransferase Prmt2 to target promoters, thereby establishing poised chromatin architecture and priming organizer gene expression [91]. Whether the transcriptional activity of maternal β-catenin is controlled by internal self-regulating protein modifications remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…These include MLL1/2 (H3K4me3), protein arginine methyltransferase 2 (PMRT2, H3R8me), SET8 (H3K20me), CARM1 (H3R17me2), and DOTL1/DOT1 (H3K79me3) (Blythe et al, 2010;Chen et al, 2010;Li et al, 2011b;Mahmoudi et al, 2010;Mohan et al, 2010;Ou et al, 2011;Sierra et al, 2006). It is not clear how consistently chromatin modifications occur among different Wnt targets, for example, for some targets, there is no change in histone acetylation upon Wnt signaling (Blythe et al, 2010;Wohrle, Wallmen, and Hecht, 2007). In contrast, a microarray study in HEK293T cells demonstrated that most genes that are activated by Wnt3a treatment required DOTL1 for this regulation (Mahmoudi et al, 2010).…”
Section: Factors and Mechanisms Activating Target Genesmentioning
confidence: 99%